Análise de um sistema de resfriamento de uma cvt para um veiculo baja sae - Almeida, Bruno Cristian (Universidade Federal Rural do Semi-Árido, 2019)
The present work aims at the cooling of the CVT (Continuous Variable Transmission) (CVT), to improve the efficiency of the set. For the development of a cooling system for the CVT applied to a Baja SAE vehicle, a belt analysis, protection and at what temperatures they were subjected were necessary. The analysis of the temperature of the CVT is important, because the prototype presented problems with the temperature increase that caused belt wear over time and its efficiency decrease. It was proposed a more detailed study of the protective temperatures during the work process, as well as an analysis and identification of components failure. This study carried out a chance to learn about the behavior of belts with the elevation of temperature. Successively with the data obtained from the experiments, the data were analyzed. Finally, with the information acquired in the steps, a discussion and validation of the acquired results was made. Where it was realized that with just the addition of the fan in the original configuration of the protection worsens the cooling.
Monografia
Keywords: Anteparos; Proteção da transmissão; Temperatura da CVT; Transmissão CVT; ENGENHARIAS::ENGENHARIA MECANICA